Xylarinoside and dehydrorhinomilisin G from the wood fungus Xylaria sp. TBRC-BCC29285 - Aibrohim Dramae; Nantiya Bunbamrung; Chakapong Intaraudom; Nattawut Boonyuen; Wilunda Choowong; Chitti Thawai; Pattama Pittayakhajonwut (Natural Product Research, 2026)
possessed weak anti-TB activity at an MIC value of 50.0 µg/mL.
Keywords: Microbial Metabolism and Applications; Microbial Natural Products and Biosynthesis; Carbohydrate Chemistry and Synthesis